Postoperative Autologous Reinfusion in Total Knee Replacement. (9th September 2015) - Crescibene, A.; Martire, F.; Gigliotti, P.; Rende, A.; Candela, M.
Abstract : Surgeries for total knee replacement (TKR) are increasing and in this context there is a need to develop new protocols for management and use of blood transfusion therapy. Autologous blood reduces the need for allogeneic blood transfusion and the aim of the present study was to verify the safety and the clinical efficacy. An observational retrospective study has been conducted on 124 patients, undergoing cemented total knee prosthesis replacement. Observed population was stratified into two groups: the first group received reinfusion of autologous blood collected in the postoperative surgery and the second group did not receive autologous blood reinfusion. Analysis of data shows that patients undergoing autologous blood reinfusion received less homologous blood bags (10.6% versus 30%;p = 0.08 ) and reduced days of hospitalization (7.88 ± 0.7 days versus 8.96 ± 2.47 days for the control group;p = 0.03 ). Microbiological tests were negative in all postoperatively salvaged and reinfused units. Our results emphasize the effectiveness of this procedure and have the characteristics of simplicity, low cost (€97.53 versus €103.79;p < 0.01 ), and easy reproducibility. Use of autologous drainage system postoperatively is a procedure that allows reducing transfusion of homologous blood bags in patients undergoing TKR.